Pemanfaatan Laporan Keuangan, Software dan Brainware Terhadap Pengambilan Keputusan Manajemen - Amalia, Dianita Nur; Ali, Hapzi (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The use of financial report, software and brainware in the context of management decision making has become a key factor in the success of modern companies. This article explains how integrating these three elements can positively impact a company's ability to make better decisions. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with qualitative method sourced from previous research literature from researchers. The results of this literature review article are: 1) financial report influences management decisions;2 ) Software influences management decisions; and 3) Brainware influences management decisions.